FAKTOR – FAKTOR YANG MEMPENGARUHI RENTANG WAKTU PENYAJIAN LAPORAN KEUANGAN KE PUBLIK (Studi Empiris pada Perusahaan-Perusahaan LQ 45 yang Terdaftar di Bursa Efek Indonesia) (Fokus Ekonomi, 2008)
Company which is go public have to make annual report to BEI ( Indonesian stockexchange ) and stockholder annually according to the decision of BAPEPAM chairman No. Kep36/PM/2003, No 1 regulation X.K.2 about the obligation of giving periodical financial report, saythat periodic financial report with accountant reporting give to BAPEPAM at least on the lastthird month after the date of annual report. The result of company audit have to announce topublic through two Indonesian newspapaer periodically and on time.The purpose of this reseachis to test factors influencing time periode of financial report giving to public with criterium ofcompany, range of provitability, solvability, auditor reputation and kinds of auditor’s opinion asindependent variableThe reseach population about company size, provitability, solvability, auditorreputation and opinion about the completion of annually financial audit report and publication ofannual financial report to public are LQ 45 company, registered at BEI 2004-2006. The datawhichis used is secundary data. Data analysis with normality, classical assumtion includingmoltikolinearitas test, heterokedastisitas test and autocorrelation, and also hipotesis test includingregression analysis and partial hipotesis ( uji t )First regression got the result that only ROA significanthy to time periode offinancial report giving to public annually ( Y1) with value of significant = 0,004<0,05. Secondregression got the result that only SIZE with value of significant 0,000<0,05, ROA value ofsignificant 0,026<0,05 dan OPINI with value of significant 0,000<0,05 that is significantlyinfluence to time periode of auditor’s financial report announcement to public ( Y2 )Key words : timelinnes, audit delay, size, provitability, solvability, auditor’s reputation, auditor’sopinion